Exploring teachers' perspectives on task-based language teaching : a case study - Musazay, Asma M. Saber (Institute of Education, International Islamic University Malaysia, 2013)
The current study aims to explore and research the perceptions of CELPAD teachers at the International Islamic University Malaysia (IIUM) towards task-based language teaching (TBLT). The research aimed to determine whether the teachers are aware of this method or not, and whether or not they use it in their classroom. In addition it explored the understanding of CELPAD teachers towards (TBLT) and how they perceive it. The study compares in terms of its advantages and the limitations for ELT. Furthermore it considered the reasons that CELPAD teachers chose to implement (TBLT) in their lessons or avoid it. The study employed a qualitative methodology, namely 'case study' the data collection instruments consisted of interviews of three randomly selected instructors at CELPAD, one for each level ranging from level 4- 6.The overall findings show that the CELPAD teachers possess a clear understanding of TBLT agreeing that TBLT is beneficial and effective for the learners, and should be implemented throughout all levels.